Cyclotrimerization of alkynes catalyzed by a self-supported cyclic tri-nuclear nickel(0) complex with α-diimine ligands. Issue 14 (20th March 2019) - Shen, Lingyi; Zhao, Yanxia; Luo, Qiong; Li, Qian-Shu; Liu, Bin; Redshaw, Carl; Wu, Biao; Yang, Xiao-Juan
Abstract : The cyclic tri-nickel(0) complex [Ni(μ-L Me-2, 4 )3 ] (L Me-2, 4 = [(2, 4-Me2 C6 H3 )NC(Me)]2 ) self-supported by the α-diimines catalyzes cyclotrimerization of alkynes to form substituted benzenes. Abstract : A cyclic tri-nuclear α-diimine nickel(0) complex [Ni(μ-L Me-2, 4 )3 ] (2 ) was synthesized from a "pre-organized", trimerized trigonal LNiBr2 -type precursor [Ni3 (μ 2 -Br)3 (μ 3 -Br)2 (L Me-2, 4 )3 ]·Br (1 ; L Me-2, 4 = [(2, 4-Me2 C6 H3 )NC(Me)]2 ). In complex2, the α-diimine ligands not only exhibit the normal N, N ′-chelating mode, but they also act as bridges between the Ni atoms through an unusual π-coordination of a C{N bond to Ni. Complex2 is able to catalyze the cyclotrimerization of alkynes to form substituted benzenes in good yield and regio-selectivity for the 1, 3, 5-isomers, which is found to vary with the nature of the alkyne employed. This complex represents a convenient self-supported nickel(0) catalyst with no need for additional ligands and reducing agent.